2017
DOI: 10.4172/2161-1459.1000228
|View full text |Cite
|
Sign up to set email alerts
|

An Ethno Botanical Review on Medicinal Plants Used for the Management of Hypertension

Abstract: Hypertension has become one of the most principal growing health problems in developing countries, and is an important cause of cardiovascular death in the world. It is also called the silent killer as it usually shows no direct symptoms and many people die of the disease without understanding its. Despite their availability and effectiveness, the conventional drugs used for the treatment of hypertension have caused adverse side effects and increased the risks of developing new diseases. Herbal medicines, ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…This study attempted to investigate the possible therapeutic uses of T. serrulatus essential oil in hyperactive airways disorders and its effectiveness against related microbial infections (Meresa et al, 2017). For this purpose, T. serrulatus essential oil extracted by hydro-distillation was tested on isolated guinea-pig tracheal tissues mounted in organ bath with physiological buffer and carbogen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study attempted to investigate the possible therapeutic uses of T. serrulatus essential oil in hyperactive airways disorders and its effectiveness against related microbial infections (Meresa et al, 2017). For this purpose, T. serrulatus essential oil extracted by hydro-distillation was tested on isolated guinea-pig tracheal tissues mounted in organ bath with physiological buffer and carbogen.…”
Section: Discussionmentioning
confidence: 99%
“…T. serrulatus is an endemic medicinal plant traditionally used for various disease conditions including flue (Meresa et al, 2017) and cough (Melka et al, 2016). In various scientific studies the plant has been found active against various bacterial and fungal strains (Damtie and Mokonen, 2016), possess diuretic and antihyperlipidemic (Melka et al, 2016;Getachew, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Phytochemical screening tests reported the presence of alkaloids, saponins, polyphenols, coumarins, anthraquinones, tannins, phytosterols and cardiac glycosides in either aqueous or ethanol extracts or infusion of M. stenopetala leaves (Meresa et al, 2017;Fekadu et al, 2017;Geleta et al, 2016b). Toma et al (2014) and Melesse et al (2017) also reported the presence of condensed tannins in either ethanol extracts or dried leaves of M. stenopetala (i.e.…”
Section: Glucosinolates and Isothiocyanatesmentioning
confidence: 99%
“…Thymus serrulatus Hochst. Ex Benth (family Lamiaceae) grows in Ethiopia and has traditionally been used to treat influenza [21] and cough [22]. T. serrulatus is a much-branched perennial subshrub that grows in the Afromontane and Afroalpine zones of Ethiopia and Eritrea [23].…”
Section: Introductionmentioning
confidence: 99%